Management of acute promyelocytic Leukemia at extremes of age - Kayser, Sabine; Conneely, Shannon (Cancers, 2023)
Tailored treatment with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) has revolutionized the outcome of acute promyelocytic leukemia (APL) from a uniformly fatal disease to one of the most curable malignant diseases in humans. Due to its high efficacy, ATO/ATRA is the standard first-line therapy in younger adult, non-high-risk APL patients. However, early death is still a major issue in APL, particularly in older patients. Thus, rapid diagnostics, immediate access to ATRA-based therapy, and supportive care are of utmost importance. Nevertheless, challenging situations occur, particularly in patients excluded from controlled studies with clinical knowledge mainly based on case reports and registries. Besides the treatment of newly diagnosed patients, managing toxicities and complications remains challenging. This review discusses the approach to the treatment of APL in elderly and pediatric patients.
Veröffentlicht: 15. Juli 2023
Gesehen am 25.08.2023